Oxidation resistance of Si doped transition metal diborides at elevated temperatures. (June 2023) - Glechner, T.; Hahn, R.; Bahr, A.; Wojcik, T.; Weiss, M.; Ramm, J.; Hunold, O.; Polcik, P.; Riedl, H.
Abstract: Si doped transition metal (TM) diborides are a promising class of thin films materials due to their outstanding oxidation resistance at high temperatures. In detail, the excellent oxidation resistance was proven i.e. for Hf-Si-B2±z being stable up to 1500 °C, whereby the low growth kinetics are attributed to a Si rich oxide formed on top. This scale formation is accompanied with a decomposition/clustering of Si within the TMB2±z structure, which can be understood as a transition from the metastable as deposited state to the thermodynamically stable phases as suggested by the ternary phase diagrams. Furthermore, the oxidation of Si was shown to be thermodynamically preferred, and hence if the transport of Si to the coating/oxide interface is ensured, a protective Si rich oxide can be expected. This requires on the one hand a certain Si content within the coatings as well as a distinct activation temperature. A generalized criterion for the required Si content is proposed, which empirically holds at least for Ti-, Cr- and Hf-Si-B2+z coatings. This criterion basically relates the minimum Si content to the amount of access boron in the diboride based coatings. Highlights: High temperature oxidation protection by TM-Si-B2±z thin films. Description of thermodynamical mechanism for selective oxidation of Si. Empirical criterion defined for minimum Si content.